2003
DOI: 10.1089/089277903765444320
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in Patients with or without a History of Open Nephrolithotomy

Abstract: A history of open nephrolithotomy does not adversely affect the efficacy or morbidity of PCNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 16 publications
2
31
1
3
Order By: Relevance
“…Previous intervention, inflammation, and adhesions of renal parenchyma could lead neovascularization and fragile vessel wall. Nevertheless, Basiri et al found no differences in blood transfusion rate according to previous open renal surgery [25]. Controversially, in Sofikerim's study, the blood transfusion rates were 3.7 and 8.1 % in patients with and without previous renal surgery, respectively [16].…”
Section: Discussionmentioning
confidence: 93%
“…Previous intervention, inflammation, and adhesions of renal parenchyma could lead neovascularization and fragile vessel wall. Nevertheless, Basiri et al found no differences in blood transfusion rate according to previous open renal surgery [25]. Controversially, in Sofikerim's study, the blood transfusion rates were 3.7 and 8.1 % in patients with and without previous renal surgery, respectively [16].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, these systemic disorders are known to alter the mechanisms of hemostasis as well as wound healing. On the other hand, ages of the patients, history of previous renal surgery or extracorporeal SWL treatment, function of the effected kidney, and degree of hydronephrosis were shown to have no significant impact on the outcome [12,18] .…”
Section: Discussionmentioning
confidence: 94%
“…The relationship of hemorrhage during PNL and patient and procedural factors has been extensively investigated in the literature [7,9,[11][12][13][18][19][20][21][22] . Establishing optimal percutaneous access appears to be the key determinant of PNL-related blood loss [12] .…”
Section: Discussionmentioning
confidence: 99%
“…With the help of newly developed high-pressure balloons, assistance of fascial dilators, or by mechanical dilators, difficulty in establishing access may be overcomed 28 . In some other studies, it had been reported that open stone surgery can increase PCNL failure rate 31 , while others showed that previous open stone surgery does not affect PCNL outcome 3234 .…”
Section: Discussionmentioning
confidence: 97%